Auditory Event-Related “Global Effect” Predicts Recovery of Overt Consciousness - Perez, Pauline; Valente, Mélanie; Hermann, Bertrand; Sitt, Jacobo; Faugeras, Frédéric; Demeret, Sophie; Rohaut, Benjamin; Naccache, Lionel (Frontiers in Neurology, 2021)
Objective: To explore whether the presence of an event-related potentials (ERP) ‘global effect’ (GE+), - that corresponds to a correlate of conscious processing in the local-global auditory task -, predicts behaviorally overt consciousness recovery in a large cohort of patients suffering from disorders of consciousness (DOC). Methods: We conducted a prospective study on all DOC patients evaluated during the 2009-2018 period. Behavioral examination included CRS-R scores and bedside high-density EEG recordings. Consciousness recovery was evaluated at 6 months by a structured phone interview. The predictive value of a GE+ was calculated both on survivors, and on all patients. Results: 236 patients with a documented outcome and technically valid EEG recordings could be included. Among them, 66 patients had a GE+ status (28%). Presence of GE+ predicted behaviorally overt consciousness recovery in survivors with high specificity (Sp=84%) and high positive predictive value (PPV=80%), but with low sensitivity (Se=35%) and low negative predictive value (NPV=42%). Positive likelihood ratio (LR+) of GE+ was superior to LR+ of initial clinical status and of ERP effect indexing unconscious auditory processing (local effect (LE)). Interpretation: Our results demonstrate that the presence of a bedside ERP GE+ is highly predictive of behaviorally overt consciousness recovery in DOC patients, irrespective of the delay, of behavioral status, and of the etiology of brain dysfunction. However, the absence of this effect is not a reliable predictor of negative outcome. This study provides Class III evidence that the presence of an ERP ‘global effect’ predicts consciousness recovery in DOC patients.